2019
DOI: 10.3390/su11082235
|View full text |Cite
|
Sign up to set email alerts
|

Pollution Tradeoffs for Conventional and Natural Gas-Based Marine Fuels

Abstract: This paper presents a life-cycle emissions analysis of conventional and natural gas-based marine transportation in the United States. We apply a total fuel cycle—or “well-to-propeller”—analysis that evaluates emissions along the fuel production and delivery pathway, including feedstock extraction, processing, distribution, and use. We compare emissions profiles for methanol, liquefied natural gas, and low sulfur marine fuel in our analysis, with a focus on exploring tradeoffs across the following pollutants: g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Their results indicated that LNG is the optimum option from environmental and economic points of view. Different with the other studies, Winebrake et al [16] examined marine emissions by well-to-propeller analysis, which analyzed the fuel emissions from production to distribution. Their results showed that the natural-gas fuel can provide environmental benefits for local residents compared to distillate fuel in the short term, but in the long-run methane leaks will lead to extra global warming.…”
Section: Emission Abatement Methods From Shipsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their results indicated that LNG is the optimum option from environmental and economic points of view. Different with the other studies, Winebrake et al [16] examined marine emissions by well-to-propeller analysis, which analyzed the fuel emissions from production to distribution. Their results showed that the natural-gas fuel can provide environmental benefits for local residents compared to distillate fuel in the short term, but in the long-run methane leaks will lead to extra global warming.…”
Section: Emission Abatement Methods From Shipsmentioning
confidence: 99%
“…However, the LNG option needs considerable initial investment and there are supply limitations at ports [15]. In this study, the LNG system is out of our discussion due to its non-comparability of emission abatement with the other alternatives [16].…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive review of published references (both academic and industrial/governmental reports) on LNG was conducted to accurately assess the estimated GHG emissions level associated with the production and consumption of LNG as a marine fuel. [7,[12][13][14][15][16][17][18][19][20][21][22][23][24][25] Figure 3 summarizes the LNG emissions ranges, with the average values shown. For the WtT part, emissions ranged between 14-30 g CO 2eq /MJ, with a mean value of 18 g CO 2eq /MJ.…”
Section: Life Cycle Analysis (Lca) Of Lng For Marine Applicationsmentioning
confidence: 99%
“…The systems perspective is handled in environmental assessments with a life cycle perspective. Some evaluations for marine fuels are found in literature, although the number of parameters evaluated differs [8,[19][20][21][22].…”
Section: Different System Perspectivesmentioning
confidence: 99%
“…Winebrake et al [20], categorized as a type 2 study, evaluated the trade-offs in pollution from some marine fuels, including distillate fuels compared to natural gas-based methanol, bio-methanol, and LNG. The assessment was focused on environmental impact and trade-offs between emissions.…”
Section: Multicritiera Decision Analysis Mcda and Marine Fuelsmentioning
confidence: 99%